The effect of supplemental irrigation, time and methods of Fe fertilizer application on qualitative and quantitative traits of chickpea (Cicer arietinum L.) - Loghman Ahmadi; Mokhtar Ghobadi; Mohsen Saeidi; Jalal Ghaderi (پژوهش‌های حبوبات ایران)
Introduction Chickpea (Cicer arietinum L.) is one of the most important grain legumes in the south Asia and WANA (West Asia North Africa). In Iran, chickpea is the most important pulse crop of rain-fed systems, traditionally grown in rotation with wheat and barley. The annual cultivation and production of chickpea in Iran is about 0.5 million hectares and 270 thousand tons, respectively. High protein content in chickpea seed (about 20-30%) makes it a good food source for developing countries and low-income people. Among the micro-nutrients, iron (Fe) is used more for plants. Fe deficiency has adverse effects on plant morphology and physiology. Earlier studies have shown that Fe deficiency reduced seed yield in chickpea, soybeans, rapeseed and wheat. In a study, application of iron fertilizer increased the branching and yield components of chickpea. In another study, application of iron fertilizer increased the branching and yield components of chickpea. A study showed that Fe deficiency reduced the water use efficiency of chickpea. In another study, iron sulfate foliar application improved the symptoms of Fe deficiency and increased the yield in low-yielding cultivars, but did not have much effect on high yielding cultivars. Foliar application of iron sulfate also increased the seed iron content. The objective of this research was to study the effects of Fe fertilizer on quantitative and qualitative characteristics of chickpea. Comparison of time and methods of Fe fertilization in chickpea was another aim of this study.